How Gender Orders and Islamic Influence Affect Women’s Participation in Indonesian Politics? - Ramadhani, Fitria Nurul (Journal of International and Local Studies, 2023)
This paper explores the long history of gender orders construction in Indonesia. How gender order and the influence of religious taught affect women political participation in Southeast Asia will be explored. In this case, the author focuses on Indonesian women and the influence of Islam as the majority religion in Indonesia. This paper argues that women political participation in Indonesia, although it seems limited by cultural and the so-called Islamic values, actually has experienced significant growth, especially after the Reformation. The gender relations that formed under the New Order that enshrined women as secondary to men which also emphasised by Islam teachings about men prerogative may seem to hinder women participation in public. However, this paper found that there were some contradictions of positioning women role under the state gender order, which has led to some positive effects on women. This contributed to the rise of women participation in Indonesia politics, especially after the reformation era.